THE EFFECT OF PROCESS INTEGRATION ON ORGANIZATIONAL CULTURE FOR STRATEGIC COLLABORATION IN AUTOMOBILE INDUSTRY - Basha, Shaik Abdul Khadar; Sridhar, Gopalasetti; Basha, Pinjari Rafiq; Khatua, Dr. Subhadarshini (The journal of contemporary issues in business and government, 2023)
A strong partnership in new vehicle retail management is a long-term commitment made by automakers and dealers towards mutual benefit. Manufacturers and dealers share a shared purpose in selling things, which makes everyone involved will benefit from a collaborative effort to sell a model automobile. This paper studies the aspects of trust that is built between the manufacturer and dealer which is affected by process integration, cultural understanding, and contract flexibility. The methodology followed was quantitative in nature in which cross-sectional data from the same manufacturing company dyad was employed. The findings of the research show a positive association between process integration with cultural understanding and contract flexibility and together these affect the trust that is built between the parties.